KORELASI MODEL PROJECT BASED LEARNING TERHADAP MINAT BELAJAR SEJARAH SISWA SMAS IT MUTIARA DURI - Annisa Pebriani Ikhsan; Hera Hastuti (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This study aims to show the effect of Project-Based Learning (PJBL) learning model on students ' learning interest in history subjects. This study is a quantitative research with a Description. The subjects of this study were students of Grade XI social studies 2 at SMA s it Mutiara Duri. From the results of field research and discussion through questionnaires, observations, to the respondents, in general, this study was analyzed using a simple linear regression technique. Based on the results of the Test t (partial) calculated t value obtained for Project-Based Learning variables 6,185 > t value table 1,990, the results of hypothesis testing showed that the value of R Square is 0.577 (57.7%). This shows that the Project-Based Learning variables as a whole provide 57.7% of the interest in learning, while the remaining 42.3% are influenced by other variables not studied in this study. It can be concluded that there is a positive relationship between variable X to variable Y.